PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBASIS APLIKASI ANDROID TENTANG MATERI SEL DAN BIOPROSES SEL UNTUK PESERTA DIDIK KELAS XI SEMESTER 1 DI SMAN 13 PADANG - Bintang Yantaris; Ardi Ardi (Universitas Sultan Ageng Tirtayasa, 2022)
Interactive media is a teaching material that usually refers to digital services in which it presents text, moving images, animations, and videos. Based on the results of student questionnaires at SMAN 13 Padang, it was found that the materials that were difficult for students to master were cell material and cell bioprocesses. This is because this material is abstract and cell biprocessing which is difficult to understand. Most schools only use teaching materials in the form of powerpoints and LKPD, therefore teachers expect other media that can help teachers and students in the learning process. Researchers conduct research with the aim of producing interactive teaching materials based onapplications android that can help students understand the material. The type of research that the researcher developed was development research with amodel 4D that used 3 stages, namely define, design, and develop, the subject that the researcher took was a biology teacher and 32 students of SMAN 13 Padang. The research that the researchers conducted obtained results in the form of interactive teaching materials basedapplications android onabout cell material and cell bioprocesses for class XI Mathematics and Natural Sciences. And from the research results, the researchers concluded that the interactive teaching materials that the researchers developed were valid and practical.